How do intrinsically disordered protein regions encode a driving force for liquid–liquid phase separation?. (April 2021) - Borcherds, Wade; Bremer, Anne; Borgia, Madeleine B; Mittag, Tanja
Graphical abstract: Highlights: Not all IDRs undergo liquid–liquid phase separation. IDRs are not necessary for protein phase separation. A stickers-and-spacers framework helps conceptualizing IDR phase behavior. The valence and patterning of stickers determine IDR phase behavior. Spacers determine the interplay of percolation and phase separation. Abstract : Liquid–liquid phase separation is the mechanism underlying the formation of biomolecular condensates. Disordered protein regions often drive phase separation, but the molecular interactions mediating this phenomenon are not well understood, sometimes leading to the conflation that all disordered protein regions drive phase separation. Given the critical role of phase separation in many cellular processes, and that dysfunction of phase separation can lead to debilitating diseases, it is important that we understand the interactions and sequence properties underlying phase behavior. A conceptual framework that divides IDRs into interacting and solvating regions has proven particularly useful, and analytical instantiations and coarse-grained models can test our understanding of the driving forces against experimental phase behavior. Validated simulation paradigms enable the exploration of sequence space to help our understanding of how disordered protein regions can encode phase behavior, which IDRs may mediate phase separation in cells, and which IDRs are highly soluble.